Income variance dynamics and heterogeneity - Costas Meghir; Luigi Pistaferri (Institute for Fiscal Studies (IFS), 2001)
Recent theoretical work has shown the importance of measuring microeconomic uncertainty for models of both general and partial equilibrium under imperfect insurance. In this paper the assumption of i.i.d. income innovations used in previous empirical studies is removed and the focus of the analysis placed on models for the conditional variance of income shocks, that is related to the approporiate measure of risk emphasized by the theory. We first discriminate amongst various models of earnings determination that separate income shocks into idiosyncratic transitory and permanent components. We allow for education-specific differences in the stochastic process for earnings and for measurement error. The conditional variance of the income shocks is then modelled as a parsimonious autoregressive process with both observable and unobserved heterogeneity. The empirical analysis is conducted on data drawn from the 1967-1991 Panel Study of Income Dynamics.
Keywords: D80; J30; 330; Microeconomic uncertainty; Earnings; ARCH.; Einkommen; Schock; Modellierung; Schätzung; USA